Awareness of Fluid Losses Does Not Impact Thirst during Exercise in the Heat: A Double-Blind, Cross-Over Study - Capitán Jiménez, Catalina (2021)
Background: Thirst has been used as an indicator of dehydration; however, as a perception, we hypothesized that it could be affected by received information related to fluid losses. The purpose of this study was to identify whether awareness of water loss can impact thirst perception during exercise in the heat. Methods: Eleven males participated in two sessions in random order, receiving true or false information about their fluid losses every 30 min. Thirst perception (TP), actual dehydration, stomach fullness, and heat perception were measured every 30 min during intermittent exercise until dehydrated by ~4% body mass (BM). Post exercise, they ingested water ad libitum for 30 min. Results: Pre-exercise BM, TP, and hydration status were not different between sessions (p > 0.05). As dehydration progressed during exercise, TP increased significantly (p = 0.001), but it was the same for both sessions (p = 0.447). Post-exercise water ingestion was almost identical (p = 0.949) in the two sessions. Conclusion: In this study, thirst was a good indicator of fluid needs during exercise in the heat when no fluid was ingested, regardless of receiving true or false water loss information.